Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(49-x^2+6x-9\)
\(=7^2-\left(x^2+2.x.3+3^2\right)\)
\(=7^2-\left(x+3\right)^2\)
\(=\left(7-x-3\right)\left(7+x+3\right)\)
\(=\left(4-x\right)\left(10+x\right)\)
\(x^2-y^2+6x+9=\left(x+3\right)^2-y^2=\left(x+3+y\right)\left(x+3-y\right)\)
\(x^3+3x^2-9x-27=\left(x-3\right)\left(x^2+3x+9\right)+3x\left(x-3\right)=\left(x-3\right)\left(x^2+6x+9\right)=\left(x-3\right)\left(x+3\right)^2\)
a) \(x^2+4x+3=\left(x^2+4x+4\right)-1=\left(x+2\right)^2-1^2=\left(x+1\right)\left(x+3\right)\) (mình sửa lại)
b) \(x^2+8x-9=\left(x^2+8x+16\right)-25=\left(x+4\right)^2-5^2=\left(x-1\right)\left(x+9\right)\)
c) \(3x^2+6x-9=3\left[\left(x^2+2x+1\right)-4\right]=3\left[\left(x+1\right)^2-2^2\right]=3\left(x-1\right)\left(x+3\right)\)
d) \(2x^2+x-3=2x^2-4x+2+5x-5=2\left(x^2-2x+1\right)+5\left(x-1\right)=2\left(x-1\right)^2+5\left(x-1\right)=\left(x-1\right)\left(2x+3\right)\)
= (x^4-4x^3)+(3x^3-12x^2)+(2x^2-8x)-(2x-8)
= x^3.(x-4)+3x^2.(x-4)+2x.(x-4)-2.(x-4)
= (x-4).(x^3+3x^2+2x-2)
Tk mk nha
\(\Leftrightarrow x^3-3x^2-3x^2+9x-10x+30\)
\(\Leftrightarrow x^2\left(x-3\right)-3x\left(x-3\right)-10\left(x-3\right)\)
\(\Leftrightarrow\left(x-3\right)\left(x^2-3x-10\right)\)
\(\Leftrightarrow\left(x-3\right)\left(x-5\right)\left(x+2\right)\)
- 3x2 + (x2 - 6x + 9)
= (x - 3)2 - 3x2 = (x - 3 - \(\sqrt{3}x\))(x - 3 + \(\sqrt{3}x\))